PENGEMBANGAN ATLAS KEANEKARAGAMAN TUMBUHAN PIONIR DI AREA BEKAS TAMBANG BIJI BESI DI DESA PULAU LAYANG KECAMATAN BATANG MASUMAI KABUPATEN MERANGIN SEBAGAI BAHAN AJAR BIOLOGI UNTUK SISWA KELAS X - Wahyu Sekar Larasati; Pitri Handayani; Eni Yulianti (BIOCOLONY, 2021)
This research is motivated by there is not yet biological teaching material which can be used as support for student while studyng at home during the Pandemic Covid 19. This study aims to produce and describe the process of developing an Atlas of Pioneer Plant Diversity as Biology Teaching Materials for Class X SMA which is valid and practical. This research is development research using 4-D model which includes define, design, develop, and disseminate. The subjects of this research consist of 5 validators, for the practicality test carried out by 2 biology teachers at SMA N 17 Merangin. The data from this research are the results of the validity and practicality of the atlas, then the data were analyzed by descriptive analysis. The results of this research is that a very valid pioneering plat Atlas has been produced from the aspect of content feasibility, language, presentation, and graphics with a validity value of 94%. The Pioneer Plant Atlas produced has also been very practical in terms of ease of use, learning time, and attractiveness with an average value of 3.88. So it can be concluded the pioneering Plant Atlas has been produced is valid and practical